Pengaruh Kepemimpinan, Pengawasan, dan Kepuasan Kerja terhadap Disiplin Kerja Pegawai - Syukur Arman Mendrofa; Sahyar Sahyar; Beby Karina Fawzeea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to analyze the influence of leadership, supervision, and job satisfaction on work discipline either simultaneously or partially. The research method used is a quantitative survey research method with a sampling technique using a census sampling technique, namely all employees with the status of echelon III, echelon IV and employees who have analytical positions as samples. The data analysis technique was carried out using multiple linear regression analysis approach, correlation test, determination test, simultaneous test and partial test. The results showed that the partial t-test value of the leadership variable on employee work discipline, the supervisory variable on employee work discipline, and the job satisfaction variable on employee work discipline respectively, namely tcount 3,723 > ttable 2,056, tcount 3,502 > ttable 2,056, tcount 8,341 > ttable 2,056. The regression equation is Y= 2.226 + 0.168 X1 + 0.324 X2 + 0.507 X3 + e. While the result of R Square is 0.969. In conclusion, simultaneously the variables of leadership, supervision, and job satisfaction have a positive effect in improving work discipline. while partially the three independent variables have a positive effect on improving work discipline. Keywords: Work Discipline, Leadership, Job Satisfaction, Supervisory Employees